Increase of antitumor activity of cisplatin using agonist of gonadotropin-realising hormone and inhibitor of aromatase on the model of ascites ovarian tumor - Tkalia, I.G.; Vorobyova, L.I.; Grabovoy, A.N.; Svintsitsky, V.S.; Tarasova, T.О.; Lukyanova, N.Y.; Todor, I.N.; Chekhun, V.F. (Experimental Oncology, 2014)
Aim : To study antitumor activity of triptorelin — agonist of gonadotropin-releasing hormone and exemestane — inhibitor of aromatase in monotherapy and in combination with cisplatin on the model of receptor-positive for estrogens and progesterone malignant ascites transplantable ovarian tumor (TOT), to assess therapeutic pathomorphosis and level of VEGF expression in tumor cells using different combinations of cytostatics and hormonal drugs. Materials and methods. 72 female Wistar rats, which underwent intraperitoneal transplantation of ascitic TOT, by 5·106 cells per animal, have been involved in the study. Rats were divided into 8 groups, 9 rats in each group. Histological study with assessment of therapeutic pathomorphosis in TOT and immunohistochemical study has been carried out. Survival of animals in the studied groups has been evaluated. Results. Among animals treated in regimen of monotherapy, the most pronounced antiangiogenic activity in TOT has been observed on application of hormonal drugs (triptorelin — 39.4 ± 1.9 and exemestane — 33.9 ± 1.4%; р = 0.003), the highest grade of treatment pathomorphosis in TOT has been observed at treatment with cisplatin (11.7%; р = 0.001). Combination of triptorelin and exemestane has amplified antiangiogenic activity in TOT (12.2 ± 0.9%; р = 0.001), but has not significantly changed rates of pathomorphosis (22.1 ± 0.4%; р=0.005) and survival of animals (32.2%; р = 0.007) as compared with the same rates in rats treated with hormonal drugs in monotherapy. Significant correlation between VEGF expression and pathomorphosis has been established (relative part of viable tumor tissue (RPVTT)) in TOT (r = 0.712; р = 0.001), as well as between RPVTT and life-span of animals (r = −0.320; р = 0.007). However, lack of correlation between VEGF expression in cells of TOT and survival of rats has been determined (r = −0.194; р = 0.11). Combination of cytostatic agent with triptorelin or exemestane has demonstrated significantly high rates of therapeutic pathomorphosis (10.1 ± 0.1% and 16.2 ± 0.3%, respectively) and antiangiogenic activity in TOT (21.4 ± 1.4% and 15.0 ± 1.3%, respectively) as well as the highest survival of animals (100.0%, increase of life-span (ILS) = 231.9% and 85.7%, ILS = 205.8%, respectively) as compared with the same one in rats treated in regimen of monotherapy with cisplatin, triptorelin, exemestane or by combination of hormonal drugs. Among animals treated by combination of cytostatic drug with triptorelin, two were cured, and among rats, which received cisplatin and exemestane, one animal was cured. Conclusions. Triptorelin and exemestane increase antitumor activity of cisplatin in respect to the malignant ascitic TOT and significantly increase survival of animals, especially when triptorelin and cisplatin are used in combination. Key Words: ascites transplantable ovarian tumor, rat, cytostatic, agonist of gonadotropin-releasing hormone triptorelin, inhibitor of aromatase exemestane, pathomorphosis, VEGF, survival.